Innovative strategies in coagulation management for cardiothoracic surgery: a narrative review of pharmacological and nonpharmacological approaches - Aleena Ihtasham; Sahla Waqas; Muhammad Hamza; Haider Imran; Saraiba Sabar Chaudhary; Tayyaba Qayyum; Sadia Batool; Nimarta Devi; Muhammad Ali Muzammil; Malik Olatunde Oduoye (Journal of Cardiothoracic Surgery)
Abstract The challenging management of coagulation in cardiothoracic surgery requires a multifaceted approach. The use of pharmacological interventions such as tranexamic acid, heparin, and aprotinin minimizes bleeding but increases the associated risks of renal impairment and seizures. However, aprotinin has been replaced by tranexamic acid for safety reasons. Supplementing nonpharmacological techniques, such as hemostatic agents and mechanical devices, with these pharmacological strategies can enhance surgical coagulation management. During cardiopulmonary bypass, factors such as hypothermia, acidosis, and fibrinolysis worsen coagulation disturbances, and protamine sulfate is administered for heparin reversal during the procedure. Point-of-care devices, including thromboelastography (TEG®) and rotational thromboelastometry (ROTEM®), provide real-time monitoring of coagulation, hence guiding clinical interventions effectively, and have demonstrated a reduction in postoperative bleeding. Nonetheless, tailored approaches are critical, especially in patients with preexisting coagulation disorders as well as in pediatric surgery. Pharmacogenomics also plays a role in selecting appropriate dosages and minimizing adverse outcomes. Recent advancements in this context include novel hemostatic agents, prothrombin complex concentrates, and direct oral anticoagulants. Future research should not only explore the combined use of pharmacological and nonpharmacological strategies but also evaluate the long-term effects and cost-effectiveness of integrated approaches during cardiothoracic surgery, particularly in high-risk populations.